2019
DOI: 10.1101/806422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Menstrual hygiene management practice and factors affecting it among high school females in Ambo City, Oromia state, Ethiopia, 2018: A cross-sectional mixed method

Abstract: Address: abuzumeran1@gmail.com 2 ¶ =this authors contributed equally to the work. 2 | P a g e I. AbstractBackground: Though menstruation is normal physiology in the females' life, if not managed safely, it can interrupt daily activity or it may lead to health problems. Poor water, sanitation and hygiene (WASH) facilities in schools, inadequate puberty education and lack of hygienic menstrual hygiene management items (absorbents) cause girls to experience menstruation as shameful and uncomfortable. This study a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…In the current study, seven studies (7,12,13,23,27,31,33) reported on school absenteeism associated with menstruation, with one in four girls missing one or more school days during menstruation (PP: 32.03%, 95%CI: 22.65%, 41.40%, I 2 98.2%), this was higher in Amhara region 37.89% (95%CI: 5.45,70.33), followed by Addis Ababa 31.72% (7.12,56.32) and Oromia region 28.38% (19.35,37.41) (Table 4).…”
Section: School Absenteeism During Menstruationmentioning
confidence: 93%
See 4 more Smart Citations
“…In the current study, seven studies (7,12,13,23,27,31,33) reported on school absenteeism associated with menstruation, with one in four girls missing one or more school days during menstruation (PP: 32.03%, 95%CI: 22.65%, 41.40%, I 2 98.2%), this was higher in Amhara region 37.89% (95%CI: 5.45,70.33), followed by Addis Ababa 31.72% (7.12,56.32) and Oromia region 28.38% (19.35,37.41) (Table 4).…”
Section: School Absenteeism During Menstruationmentioning
confidence: 93%
“…Concerning the quality score of included studies, most articles (77.3%) had low-quality scores (Table 1). In addition, 18 studies (7,12,13,(19)(20)(21)(23)(24)(25)(26)32,33,(35)(36)(37)(38)40,41) performed multivariate analyses to identify factors associated with MHM in Ethiopia (Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations